SME Resilience under Global Economic Disruption: A Conceptual Analysis Based on Resource-Based View and Dynamic Capabilities - Sofia Mahardianingtyas; Sudarmiatin; Heri Pratikto (Abadi Institute, 2026)
This study analyzes how small and medium-sized enterprises (SMEs) respond to global economic disruptions, particularly those driven by geopolitical instability and energy price volatility. The research adopts a conceptual and desk-based approach by synthesizing recent literature on SME resilience and organizational capabilities. The findings indicate that SMEs are highly vulnerable to external shocks due to limited resources, yet they possess adaptive potential through internal capabilities. In particular, dynamic capabilities enable SMEs to sense environmental changes, seize emerging opportunities, and transform business operations. These capabilities are often manifested through business model innovation, digital technology adoption, and supply chain adjustments. Furthermore, external support such as government policies and technological infrastructure strengthens SMEs’ resilience and recovery capacity. This study proposes a conceptual framework linking global economic shocks to SME resilience through internal capabilities and strategic adaptation. The findings provide practical implications for SMEs and policymakers in developing countries to enhance business sustainability and economic stability under uncertain global conditions.